Global, Regional, and National Burden of Low Bone Mineral Density From 1990 to 2019: Results From the Global Burden of Disease Study 2019 - Dong, Yimin; Kang, Honglei; Peng, Renpeng; Song, Kehan; Guo, Qian; Guan, Hanfeng; Zhu, Meipeng; Ye, Dawei; Li, Feng (Frontiers in Endocrinology, 2022)
Objective: We aim to explore the global spatial prevalence and temporal trends of the exposure and burden of low bone mineral density (LBMD) worldwide, due to a lack of related studies. Methods: We used data from the Global Burden of Disease Study 2019 to conduct this study. The estimation for the exposure and burden of LBMD was made in DisMod-MR 2.1, a Bayesian meta-regression tool. Correlation analysis was performed using the Spearman rank order correlation methods. The temporal trends were represented by the estimated annual percentage change (EAPC). Results: In 2019, there were 438 thousand deaths and 16.6 million DALYs attributable to LBMD, increasing by 111.1% and 93.8% respectively, compared to that in 1990. From 1990 to 2019, the age standardized summary exposure value to LBMD has decreased worldwide, but has increased in high-income North America. Some countries, such as the United States, Australia, Canada, and China had increased disability and mortality rate of LBMD with time. Countries with low socio-demographic index (SDI) had higher exposure and mortality rate than those with high SDI. The exposure to LBMD was lower in males, but the attributable disability and mortality were higher in males in all years from 1990 to 2019. Conclusion: With population aging, countries worldwide, especially those with low-SDI, will face increasing challenges in reducing the exposure and burden of LBMD and osteoporosis. The treatment of osteoporosis has been overlooked in men for a long time. Effective measures are warranted to control the prevalence and burden of LBMD.